Literacka emancypacja romantycznych grup poetyckich w periodykach warszawskich lat 1829–1830. W kręgu „Melitele” - Ożóg-Winiarska, Zofia; Winiarski, Jerzy (Dydaktyka Polonistyczna, 2019)
The article’s aim is to renew the research issues concerning regional romantic groups active in Warsaw in the years 1829–1830, in particular to describe the situation of the group of poets of Warsaw and Lithuanian background gathered around the two issues of the annual Melitele edited by Adam Mickiewicz’s friends, Antoni Edward Odyniec and Stefan Witwicki. The annual managed to develop forms, subjects and ideas of romanticism adopted years earlier by the Vilnius-based Society of Philomaths, and promote Mickiewicz’s poetry of his Russian period. In this way Melitele became the centre (medium) developing literary life in Warsaw and spreading patterns and patriotic ideas of freedom, and thus affecting integration of the Warsaw-based circles of young men of letters and patriots around the axiology of Polish romanticism. The annual created regional climate that revived poetry and critical reviews on a nationwide scale in the time preceding the November Uprising.